The Impact Of Value Added Tax (VAT) On Cross Border E-Commerce Transactions: Evidence From The Etsy Platform In Indonesia - Rahmat Burhamzah; Muhammad Rijal Alim Rahmat (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
The rapid expansion of digital commerce has transformed international trade and created significant challenges for tax authorities in monitoring and collecting taxes from cross-border transactions. In response, Indonesia implemented an 11% Value Added Tax (VAT) on electronic commerce transactions through Electronic Commerce Systems (PMSE) to improve tax compliance, increase state revenue, and establish competitive neutrality between domestic and foreign sellers. This study examines the impact of VAT implementation on cross-border e-commerce transactions using the Etsy platform as a case study. A quantitative case study approach was employed, utilizing secondary data collected from the Directorate General of Taxes (DGT), Statistics Indonesia (BPS), Bank Indonesia (BI), OECD reports, the SEA e-Conomy Report, and publicly available Etsy platform documentation. Data were analyzed using descriptive and comparative approaches to evaluate changes in tax revenue, transaction volume, seller competitiveness, and administrative efficiency. The findings indicate that PMSE VAT revenue increased significantly from IDR 3.8 trillion in 2020 to IDR 10.5 trillion in 2022, reflecting a 176% increase within two years. Platform-based VAT collection achieved an estimated compliance rate of 95%, substantially outperforming conventional tax collection systems. However, VAT implementation was associated with a decline in Etsy transaction volume of approximately 15% and increased operational costs for sellers, reducing profit margins and affecting the competitiveness of micro, small, and medium enterprises (MSMEs). The study also reveals that VAT implementation successfully eliminated the price advantage previously enjoyed by imported products, thereby promoting competitive neutrality within Indonesia’s digital marketplace. Nevertheless, fragmented tax collection mechanisms between digital platforms and customs authorities continue to create administrative inefficiencies, compliance burdens, and potential risks of double taxation. The study recommends greater integration between digital platforms, tax authorities, and customs systems to enhance administrative efficiency while maintaining sustainable growth in the digital economy.